Nauczanie języka angielskiego w pierwszym podręczniku angielskiego dla Polaków z 1788 roku = Teaching English in the first English handbook for Poles of 1788 - Kotlarska, Irmina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of a preliminary analysis of the first grammar of English, namely "Grammatyka dla Polaków chcących się uczyć angielskiego języka" ["Grammar for Poles who want to learn the English language"] written by Julian Antonovich, a Polish teacher, and published in Warsaw in 1788.
Keywords: język angielski - nauczanie; podręczniki; języki obce; Nauczanie - historia; 18 w.; history of foreign language teaching; English language; Antonowicz, Julian (ok. 1750-1824)